2016
DOI: 10.4081/ripppo.2016.241
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic interventions in intimate partner violence: an overview

Abstract: Intimate partner violence (IPV) is associated with significant morbidity and mortality, and its prevention is a global public health priority. There is strong scientific evidence that suggests IPV and symptoms such as anxiety, depression, post-traumatic stress disorder, substance abuse, chronic pain, etc. are linked. Despite recommendations and various interventions for the treatment of IPV that have been tried in these last 20 years, the rates of recurrence are still too high. Furthermore, there is a lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 77 publications
(90 reference statements)
0
26
0
Order By: Relevance
“…Although such suggestions also apply to male victims of IPV, they typically have been focused on preventing violence against girls and women perpetrated by boys and males. In fact, despite the increasing awareness that men can both sustain and perpetrate IPV, a recent overview of therapeutic interventions for IPV (Condino, Tanzilli, Speranza, & Lingiardi, 2016) found that most programs focus on male perpetrators and female victims and lack specific interventions for male victims of IPV or bidirectional IPV in which men are both victims and perpetrators (Condino et al, 2016).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Although such suggestions also apply to male victims of IPV, they typically have been focused on preventing violence against girls and women perpetrated by boys and males. In fact, despite the increasing awareness that men can both sustain and perpetrate IPV, a recent overview of therapeutic interventions for IPV (Condino, Tanzilli, Speranza, & Lingiardi, 2016) found that most programs focus on male perpetrators and female victims and lack specific interventions for male victims of IPV or bidirectional IPV in which men are both victims and perpetrators (Condino et al, 2016).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Anderson et al, 2019;Kupers, 2015;Sanchéz & Wolff, 2017;Sanchéz & Wolff, 2016). Although not all publications are specific in this scope, not explicitly identifying which models are evidence-based, the literature on victimization and trauma highlights the cognitivebehavioral models as those with greater empirical validity (Condino et al, 2016;Shubina, 2015). Additionally, one of the articles explicitly identifies the cognitive-behavioral model as being clearly the most adequate one (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Herman-Lewis [ 15 ] points out how, in therapy work with women who have suffered IPV, recovery from the trauma goes through various stages: construction of safe conditions, elaboration of the grief to transform the memory of the trauma and the rebuilding of social relationships. Although many studies focus on the consequences that IPV has on the psychophysical health of those who experience violence, few studies have focused on different types of clinical intervention and their effectiveness [ 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%